Study on the Influence of Inlet Drag at Front and Rear Sides of Compressor on the Performance of Supercharged Engine. Issue 5 (January 2021) - Wang, Shangxue; Zhang, Zhijun; Cao, Jing; Chen, Jinbing
Abstract: In this paper, the influence of inlet drag at the front and rear sides of a compressor on the performance of a supercharged engine is tested. The test results show that the air flow into the engine, the combustion pressure and the engine output power decrease, the specific fuel consumption and the exhaust temperature behind the turbine increase with the increase of air intake drag. Especially when the engine at low speed operation, with the increase of inlet drag, engine performance will worsen sharply. Compared with the influence of the drag after compressor on the engine performance, the drag before compressor is more sensitive to the influence of the engine performance. When the engine speed is 1500r/min, 1900r/min and 2400r/min, the reduction in engine power caused by inlet drag in front of the compressor is 2.63 times, 4.1 times and 7.5 times that caused by the same inlet drag after the compressor. Also, the former results in an increase in specific fuel consumption 2.18 times, 3.1 times and 5.16 times of the latter. So optimizing the structure of the inlet system in front of the compressor can reduce the performance loss of the engine more effectively. The conclusions of this paper will provide guidance for the selection and matching of air filters, the spatial arrangement of multi-stage air filters in turbocharged engines, and the structural design of air intake system.